2016
DOI: 10.3233/ch-152017
|View full text |Cite
|
Sign up to set email alerts
|

Effects of lipopolysaccharide on changes in red blood cells in a mice endotoxemia model

Abstract: The aim of this study was to evaluate changes in RBC aggregation and deformability over 24 hr and suggest specific shear stress values for detecting RBC deformability in a mouse endotoxemia model using lipopolysaccharide (LPS).Six-week-old male BALB/c mice received LPS (20 mg/kg) intraperitoneally. Aggregation indices (AIs) and T1/2 were measured to assess RBC aggregation, and elongation indices (EIs) were used to assess RBC deformability at shear stress values of 0.3, 0.5, 1, 3, 7, 10, 15 and 20 Pascals (Pa) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
0
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 14 publications
0
0
0
Order By: Relevance
“…LPS binds three times more to the RBC membrane and activates WBCs, accelerates oxygen-free radical formation, and activates the Toll-like receptor (TLR-4), causing complement-mediated hemolysis and reducing erythrocytes, potentially inhibiting hematopoiesis [ 16 ]. LPS binds more to RBC membranes due to biochemical alterations caused by free radicals and cytokines.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…LPS binds three times more to the RBC membrane and activates WBCs, accelerates oxygen-free radical formation, and activates the Toll-like receptor (TLR-4), causing complement-mediated hemolysis and reducing erythrocytes, potentially inhibiting hematopoiesis [ 16 ]. LPS binds more to RBC membranes due to biochemical alterations caused by free radicals and cytokines.…”
Section: Discussionmentioning
confidence: 99%
“…LPS binds more to RBC membranes due to biochemical alterations caused by free radicals and cytokines. That decreases membrane elasticity and deformability and may lead to a loss of normal membrane flexibility [ 16 ]. Alongside RBCs, the Hb concentration and PCV are also reduced.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have indicated that the administration of TMG or NButGT (27), an OGA inhibitor, improves the survival of LPS-injected mice (28,29) and has a protective effect on cardiovascular function or lung-tissue damage, which suggests that O-GlcNAcylation is deeply engaged in LPS-induced pathophysiological changes (30,31). However, the role of O-GlcNAcylation in the functional disruption of erythrocytes induced by LPS-induced endotoxemia (32,33) should be further investigated. Using erythrocytes isolated from the whole blood of LPS i.p.…”
Section: Reduction Of O-glcnacylation Modulates Damage To Erythrocyte...mentioning
confidence: 99%